2022
DOI: 10.1177/22808000221094685
|View full text |Cite
|
Sign up to set email alerts
|

Swirling flow of fluid containing (SiO2) and (MoS2) nanoparticles analyze via Cattaneo-Christov theory

Abstract: Investigation of heat transport mechanism in swirling flow of viscous fluid containing silicon dioxide [Formula: see text] and molybdenum disulfide [Formula: see text] nanoparticles is performed. The flow is engendered due to stretchable rotating cylinder which immersed in infinite fluid. The boundary layer assumption is applied to simplify the governing equations of the problem. The theory of Cattaneo-Christov for thermal energy transportation is employed in the present phenomenon under the heat and mass cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The bvp4c approach is used to calculate the Nusselt number’s values. Table 4 is presented to validate the results of problem by comparing them with the previously published papers, Fang and Yao 8 and Zhang et al 13 The table is constructed by varying the values of Reynolds number and neglecting hybrid nanofluid conduct and magnetic effects for coefficients of shear stresses. It is found that f ~ ( 1 ) and g ~ ( 1 ) decrease by augmenting the R e The results obtained are in good agreement with Fang and Yao 8 and Zhang et al 13 as a special case, that is , for M = 0 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The bvp4c approach is used to calculate the Nusselt number’s values. Table 4 is presented to validate the results of problem by comparing them with the previously published papers, Fang and Yao 8 and Zhang et al 13 The table is constructed by varying the values of Reynolds number and neglecting hybrid nanofluid conduct and magnetic effects for coefficients of shear stresses. It is found that f ~ ( 1 ) and g ~ ( 1 ) decrease by augmenting the R e The results obtained are in good agreement with Fang and Yao 8 and Zhang et al 13 as a special case, that is , for M = 0 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a high ductility is achieved with a high strain hardening rate by including these components in the high-strength steel grade. 13 as a special case, that is, for M = 0 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations